Global Existence and Boundedness of Solutions to a Second-Order Nonlinear Differential System - Changjian Wu; Shushuang Hao; Changwei Xu (Journal of Applied Mathematics)
We investigate the global existence and boundedness of solutions to a second-order nonlinear differential system.